Rice NIN‐LIKE PROTEIN 4 plays a pivotal role in nitrogen use efficiency - Wu, Jie; Zhang, Zi‐Sheng; Xia, Jin‐Qiu; Alfatih, Alamin; Song, Ying; Huang, Yi‐Jie; Wan, Guang‐Yu; Sun, Liang‐Qi; Tang, Hui; Liu, Yang; Wang, Shi‐Mei; Zhu, Qi‐Sheng; et al. (Plant biotechnology journal, 2021)
Summary Nitrogen (N) is one of the key essential macronutrients that affects rice growth and yield. Inorganic N fertilizers are excessively used to boost yield and generate serious collateral environmental pollution. Therefore, improving crop N use efficiency (NUE) is highly desirable and has been a major endeavour in crop improvement. However, only a few regulators have been identified that can be used to improve NUE in rice to date. Here we show that the rice NIN‐like protein 4 (OsNLP4) significantly improves the rice NUE and yield. Field trials consistently showed that loss‐of‐OsNLP4 dramatically reduced yield and NUE compared with wild type under different N regimes. In contrast, the OsNLP4 overexpression lines remarkably increased yield by 30% and NUE by 47% under moderate N level compared with wild type. Transcriptomic analyses revealed that OsNLP4 orchestrates the expression of a majority of known N uptake, assimilation and signalling genes by directly binding to the nitrate‐responsive cis‐element in their promoters to regulate their expression. Moreover, overexpression of OsNLP4 can recover the phenotype of Arabidopsis nlp7 mutant and enhance its biomass. Our results demonstrate that OsNLP4 plays a pivotal role in rice NUE and sheds light on crop NUE improvement.